Kegiatan Donor Darah Di Kecamatan Lau Cimba Bekerjsama Dengan PMI Kabupaten Karo - Daniel Ginting; Farida Ariani Pelawi; Nina Fentiana (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2023)
Blood donation activities are carried out to maintain the stability of PMI blood stock in Karo Regency. The blood donation activity was held on Friday, July 28 2023 at the GBKP Kabanjahe Kota Hall, Lau Cimban District. The blood donation service activity was attended by a total of 21 participants. From the results of the implementation of the activity, 21 blood bags have been collected. Based on interviews with the participants, their motivation to donate blood was due to a sense of humanity for people in need, to maintain their own health, invitations from friends, and some were interested because of the gifts offered at the end of the event. The implementation of blood donation activities in Lau Cimba District, Karo Regency as one of the community services has been carried out well and received a good response from the participants. More is needed for socialization so that the number of blood donors increases and more people are willing to become blood donors.